Poesia aldravia na educação de jovens e adultos: leitura da palavra articulada à leitura de mundo: Aldravia poetry in youth and adult education: reading the word articulated to the reading the world (Revista Cocar, 2024)
Este artigo objetiva desvelar potencialidades do trabalho com poesia aldravista na Educação de Jovens e Adultos, a fim de favorecer práticas de leitura da palavra articuladas à leitura de mundo. Metodologicamente, com base em revisão bibliográfica, é traçado um movimento analítico interseccional entre princípios da Educação Popular como dialogicidade, problematização da realidade e participação popular às produções poéticas aldravistas. Ao propiciar um movimento ativo de atribuição de sentidos por parte de leitoras/es, em interlocução com textos e temas advindos de suas histórias de vida, o trabalho com aldravia pode contribuir com a investigação do universo temático de educandas/os de EJA, potencializando a problematização de suas realidades e dos desafios vivenciados em seu cotidiano, favorecendo processos de participação e transformação sociais.Palavras-chave:  Educação Popular; Educação de Jovens e Adultos; Aldravia. AbstractThis article aims to unveil the potentialities of working with Aldravista poetry in Youth and Adult Education, in order to promote educational practices of reading the words articulated with reading the world. Methodologically, based on a bibliographical review, an intersectional analytical movement is outlined between principles of Popular Education such as dialogicity, problematization of reality, and popular participation to Aldravista poetic productions. By fostering an active movement of meaning attribution by readers, in dialogue with texts and themes arising from their life stories, work with Aldravista poetry can contribute to the investigation of the thematic universe of Youth and Adult Education learners, enhancing the problematization of their realities and the challenges experienced in their daily lives, favoring processes of social participation and transformation.Keywords: Popular Education; Young and Adult Education; Aldravia.
Keywords: Educação Popular; Educação de Jovens e Adultos; Aldravia